Initial Cost Comparison of Rigid and Flexible Pavements Case Study: Khartoum State - Medani, Tarig O.; Hussein , iedan, Ahmed G. (University of Khartoum Engineering Journal, 2022)
n Sudan, only flexible pavements are used despite some doubts regarding their economic value under different conditions. In this paper, the properties and design of cement concrete rigid pavement and flexible pavement were described. The initial costs of both types of pavements were compared, based on the prices of the Ministry of Infrastructures and Transportation, Khartoum State. While the soil sub-grade and traffic loading govern the pavement design, the material composition is the most relevant factor in the comparison. Although only the initial cost was used for the comparison, it was found that rigid pavements were more economical than flexible pavements regardless of subsoil conditions for traffic volume less than 3,000,000 ESAL. The preference of rigid pavements will definitely be more beneficial when the total life cycle cost is considered. It is advisable for road authorities to develop parametric guidelines regarding the selection of pavement type.